Proceedings of the Fourteenth Annual ACM-SIAM Symposium on Discrete Algorithms 2020
DOI: 10.1137/1.9781611975994.154
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic Algorithms for Decremental Approximate Shortest Paths: Faster and Simpler

Abstract: In the decremental (1 + )-approximate Single-Source Shortest Path (SSSP) problem, we are given a graph G = (V, E) with n = |V |, m = |E|, undergoing edge deletions, and a distinguished source s ∈ V , and we are asked to process edge deletions efficiently and answer queries for distance estimates dist G (s, v) for each v ∈ V , at any stage, such that s, v). In the decremental (1 + )-approximate All-Pairs Shortest Path (APSP) problem, we are asked to answer queries for distance estimates dist G (u, v) for every … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…Interestingly, it seems that the other known approaches to fully dynamic APSP in real-weighted graphs [19,24,47], if adjusted, cannot easily yield subquadratic (in n) update times for "sparse" instances of MPSP where m, k = O(n). This is because they all reconstruct shortest paths in a hierarchical manner, by inductively stitching [24] or extending [19,47] paths recomputed earlier in the process. Even though the number of input source-target pairs of interest may be small, these may require answers for Θ(n 2 ) distinct source-target pairs at lower levels of the hierarchy.…”
Section: Our Resultsmentioning
confidence: 99%
“…Interestingly, it seems that the other known approaches to fully dynamic APSP in real-weighted graphs [19,24,47], if adjusted, cannot easily yield subquadratic (in n) update times for "sparse" instances of MPSP where m, k = O(n). This is because they all reconstruct shortest paths in a hierarchical manner, by inductively stitching [24] or extending [19,47] paths recomputed earlier in the process. Even though the number of input source-target pairs of interest may be small, these may require answers for Θ(n 2 ) distinct source-target pairs at lower levels of the hierarchy.…”
Section: Our Resultsmentioning
confidence: 99%
“…The decremental shortest path problem was originally studied in the context of efficiently handling single-source shortest path queries while edges are deleted [20,3,16]. All-pairs shortest path variants of the problem have also been studied [5,2].…”
Section: Related Problemsmentioning
confidence: 99%
“…Even more recently, Chuzoy and Khanna [CK19] extended their framework and showed that it can be used to improve the static problems of vertex-capacitated max-flow and sparsest vertex cut. Probst Gutenberg and Wulff-Nilsen [GW20b] recently presented a deterministic algorithm that improves on the former bounds for sparse graphs with total update time mn 0.5+o(1) . The existing data structures where futher extended in [Ber+20] to be path-reporting.…”
Section: Running Timementioning
confidence: 99%